(untitled) (Bangladesh Journal of Medical Science, 2021)
Fisheries sector is considered as fast-growing sector in India. At present fish production has increased over time, but it doesn’t change the economic conditions of the fishing community. Fisheries’ daily income is very low and varied depending upon capture of fish and their income isn’t steady. Fisheries aren’t only engaged in fishing, they also engage in other jobs because fisheries get less amount of profit of margin and this occupation is not continue all over the year. Various study reported that their educational and economical status was not satisfactory. Large family sizes, lack of regularity in alternative occupation, lack of own fishing gear is the main cause of poverty of fishermen. Most of them lived in mud made house or katcha house and addicted to tobacco or alcohol. Few studies revealed the dietary iron deficiency, low iron absorption, protein and micronutrient deficiencies and infections which lead to poor nutritional status of the fisherman. Study also reported that fishermen are a special group with some unfavorable life styles and vulnerable for injuries, skin and respiratory problems, filarial and certain other diseases. Based on the literature, it may be stated that there is need to specifically target and improve the occupational lifestyle of fishermen and various interventions like nutrition and health promotion activities, educational issues to be addressed. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.707-713